ФАКТОРЫ, ВЛИЯЮЩИЕ НА ВОВЛЕЧЕННОСТЬ СОТРУДНИКОВ В СИСТЕМЕ ГОСУДАРСТВЕННОГО УПРАВЛЕНИЯ - ЯнкеловеН.; ЙоняковаЗ.; ПуховичоваД. (Вопросы государственного и муниципального управления, 2022)
The aim of this study is to examine the relationship between the work engagement of state administration employees and managerial support from their superiors. Attention is focused not only on the direct effect of these two variables, but also on the role of perceived fairness and public service motivation in the examined relationship. For data collection, a questionnaire survey was conducted among managers in the state administration in Slovakia (221 respondents). The PLS-SEM method using SmartPLS 3.0 software was used to test the theoretical research model and the proposed hypotheses. The direct correlation between managerial support and employee engagement in state administration was confirmed as significant. Our study showed that even the support from managers can influence work exposure, but the intensity of the effect is enhanced by the engagement of perceived fairness in the work environment and public service motivation of employees. At the same time, women are more sensitive to the effects of the studied variables compared to men. Therefore, it is essential that government management builds a culture of support and fairness that encourages employee engagement. The contribution of this article is to explore the deeper mechanisms, that influence employee engagement in public administration.